CONSTRUCT AND INITIAL VALIDATION OF CHARACTER STRENGTH SCALE DEVELOPMENT INSTRUMENT FOR JUNIOR HIGH SCHOOL STUDENTS' ACADEMIC RESILIENCE - Rahma Hanif; Eva Imania; Mami Hajaroh; Agus Basuki; Nur Azizah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to develop and evaluate the content validity of an academic resilience instrument for junior high school students (SMP) that includes three main dimensions: perseverance, self-reflection and adaptive assistance, and negative affect and emotional responses. Through an assessment process by three experts using the Aiken's V technique, 45 out of 54 items (83.3%) were declared to have high content validity (Aiken's V ≥ 0.80), while the other nine items showed low validity (Aiken's V = 0.333) and were recommended for revision. These findings indicate that in general the instrument has met the criteria for adequate content validity and is suitable for use to measure the academic resilience of junior high school students. The main recommendation of this study is to maintain items that have been proven valid, and to conduct further revisions and empirical testing using exploratory factor analysis (EFA) or confirmatory factor analysis (CFA) methods to ensure the structure and internal consistency of the instrument statistically.